A COMPARISON OF THE FINANCIAL SECTOR AND MACROECONOMIC PERFORMANCE USING TURNING POINTS ANALYSIS - Michał Bernardelli; Mariusz Próchniak (Polityki Europejskie, Finanse i Marketing)
Loss of financial potential is one of the most serious risks enterprises face. The risk management system for the loss of financial potential helps enterprises identify, evaluate and manage risks that may affect their financial condition. This system allows enterprises to reduce the possibility of financial losses andensures more efficient work with financial resources. The purpose of the article is to identify the main imperatives, which are the basis for ensuring the development of financial potential and the justification of measures to neutralise the risks of business entities in the agricultural sector in Ukraine. The main sources of loss of financial potential of enterprises in the agricultural sector of the economy of Ukraine have been identified. It has been established that currently, the biggest threats are: low business activity, a low level of technological equipment and innovation, negative profitability and slow turnover of capital, lack of access to credit for small- and medium-sized enterprises and climate changes. Agricultural enterprises are subject to various risks of loss of financial potential, which may be associated with changes in weather conditions, animal epidemics, changes in legislation, currency risks, etc. Neutralisation of these risks is an important element of effective management of an agricultural enterprise and ensuring its stability. It has been proven that one of the ways to neutralise risks is to create a reserve fund in case of unexpected events that may lead to the loss of financial potential. Such a fund may include funds that can be used for replanting crops, repairing infrastructure, reimbursing losses from animal epidemics and other needs. It is proposed to minimise the risks with the help of insurance. Insurance can be provided at different levels: from crop insurance to emergency insurance. Having insurance allows the company to reduce financial losses in case of unexpected events. In addition, the enterprise can use financial instruments to reduce currency risks. These tools will enable you to protect the company from changes in exchange rates.